Development inactivated vaccine prototype of avian influenza (AI) H5N1 local isolate and its application at laboratory level - R Indriani; N.L.P.I Dharmayanti; T Syafriati; A Wiyono; R.M.A Adjid (Indonesian Center for Animal Research and Development (ICARD), 2005)
A preliminary study related on vaccine safety and vaccination effectivity for controlling avian influenza (AI) subtype H5N1 was carried out at Virology Laboratorium, Indonesian Veteriner Institute, Bogor. A Prototype of inactivated vaccine was made using AI H5N1 local isolate (A/Chicken/West Java/67-2/2003). The vaccine was then tested for safety and protection in DOC of layers. Antibody response, protection and shedding virus challenge were observed in the experiment. Result showed that the vaccine was saved and protected against virulent viral challenge. Efective vaccination was achieved at 3 weeks chicken old started with low level of antibody. Antibody titre increased gradually and reached the top at 8 weeks post vaccination. Challenge test using AI virulent at the age of 4 and 8 weeks post vaccination showed that the vaccine gave high protection (90%). Viral shedding was not longer expressed than 7 days after challenge. It is concluded that this prototype is a satisfied AI vaccine in laboratory level. Key Words: Vaccine, Avian Influenza, H5N1, HPAI